Penentuan Struktur Permukaan dengan Menggunakan Kaedah Kapasitans - Wan Yusof, Wan Mohamad Daud; Talib, Zainal Abidin; Ismail, Mohd Zaid (Universiti Putra Malaysia Press, 1999)
This work describes a method to obtain surface microtopography of a material by scanning its capacitance. Capacitance was measured by the three terminal method with the core of a coaxial cable used as the measuring probe while the shielding wire acted as the guard electrode to eliminate the fringing field effect. From our results, we found that good image resolution is best obtained if the medium used has a high dielectric constant than the sample.